Experimental Investigation on Failure Behaviors of G50 Ultra-High Strength Steel Targets Struck by Tungsten Alloy Spherical Fragments at High Velocity - Peng, Hu; Shouqian, Wang; Xiaowei, Feng; Juncheng, Li; Zhengcao, Lu; Zhuoran, Li; Xianfeng, Zhang (Frontiers in Materials, 2021)
An experimental investigation is presented into the failure behaviors of the G50 ultra-high strength steel targets struck by tungsten alloy spherical fragments at high velocity. The depth of penetration and the crater volume of G50 steel targets at velocities ranging from 923m/s to 1807m/s are obtained by ballistic gun experiments. A conic-like crater is observed in the G50 steel target after impact by a tungsten alloy spherical fragment, which is different from that in the experiments of low strength steel targets. It is believed that the eroding and fragmentation of the tungsten fragment during the penetration process give rise to this phenomenon. In addition, several tensile cracks are found both at the crater surface and the crater bottom, which are considered to be caused by tensile stress induced by the superposition of rarefaction waves at some local areas of the impacted interface. Numerical simulations of the penetration of tungsten alloy fragments into G50 steel targets are performed to predict failure features of the targets. It is shown that the numerical results are in good agreement with available experimental results.